International Bean Improvement Cooperative (BIC) and North American Pulse Improvement Association (NAPIA) Biennial Meeting, hosted by the University of Nebraska-Lincoln. Presentations by the Bean Program - Gomez Jimenez, Maria Isabel; Tirado, Cristian; Buendia, Hector Fabio; Polania, Jose; Paz, Lina; Beebe, Stephen; Wilker, Jennifer; Espitia, Ernesto; Kato, Fred; Paparu, Pamela; Mukankusi, Clare; Mosquera, Gloria; et al. (2025)
Rising temperatures are becoming a serious challenge for bean production in tropical regions, affecting both yields and grain quality. This contribution presents practical insights from field and greenhouse evaluations of diverse bean materials aimed at identifying lines that perform better under heat stress. By focusing on visible yield traits such as seed set, pod performance, and grain quality, the work highlights how certain beans are able to maintain more stable production in warmer conditions. The findings are relevant for breeders, researchers, and development partners interested in climate-resilient crops and support efforts to deliver bean varieties better adapted to current and future climate challenges.